Estrategias creativas para la promoción de la igualdad de género en estudiantes de Básica Superior - Gonzales Armijos, Ximena Marisol (2023)
Creative strategies are a fundamental basis to promote and motivate gender equality in students, inducing respect among peers, which is important in all spaces for the achievement of an egalitarian society. The objective of this study is to analyze the creative strategies that affect the promotion of gender equality in students of the Superior Basic Circuit of the C_01Guayzimi Circuit, of the Nangaritza canton, of the Republic of Ecuador. The development of this work had a qualitative approach, the type of exploratory research, using inductive, deductive, analytical and synthetic methods, it should be noted that the instruments for collecting information were the interview and the focus group. In relation to the data obtained, evident results are specified that determine the ignorance of creative strategies as a means to strengthen the promotion of gender equality in students, which considerably affects educational performance. From this perspective, it is concluded that the teacher must have diverse knowledge about the strategies or actions that must be applied, to provide a primary contribution to each of the students in gender equality, respecting the diversities to which they may be exposed